Biodiversity and biocatalyst activity of culturable hydrocarbonoclastic fungi isolated from Marac–Moruga mud volcano in South Trinidad - Amanda C. Ramdass (Nature Portfolio, 2021)
Abstract Mud volcanoes (MVs) are visible signs of oil and gas reserves present deep beneath land and sea. The Marac MV in Trinidad is the only MV associated with natural hydrocarbon seeps. Petrogenic polyaromatic hydrocarbons (PAHs) in its sediments must undergo biogeochemical cycles of detoxification as they can enter the water table and aquifers threatening ecosystems and biota. Recurrent hydrocarbon seep activity of MVs consolidates the growth of hydrocarbonoclastic fungal communities. Fungi possess advantageous metabolic and ecophysiological features for remediation but are underexplored compared to bacteria. Additionally, indigenous fungi are more efficient at PAH detoxification than commercial/foreign counterparts and remediation strategies remain site-specific. Few studies have focused on hydrocarbonoclastic fungal incidence and potential in MVs, an aspect that has not been explored in Trinidad. This study determined the unique biodiversity of culturable fungi from the Marac MV capable of metabolizing PAHs in vitro and investigated their extracellular peroxidase activity to utilize different substrates ergo their extracellular oxidoreductase activity (> 50% of the strains decolourized of methylene blue dye). Dothideomycetes and Eurotiomycetes (89% combined incidence) were predominantly isolated. ITS rDNA sequence cluster analysis confirmed strain identities. 18 indigenous hydrocarbonoclastic strains not previously reported in the literature and some of which were biosurfactant-producing, were identified. Intra-strain variability was apparent for PAH utilization, oil-tolerance and hydroxylase substrate specificity. Comparatively high levels of extracellular protein were detected for strains that demonstrated low substrate specificity. Halotolerant strains were also recovered which indicated marine-mixed substrata of the MV as a result of deep sea conduits. This work highlighted novel MV fungal strains as potential bioremediators and biocatalysts with a broad industrial applications.